Improved photodetection capabilities of Ag@CeO2 Nanorod composite array using GLAD technique. Issue 20 (15th October 2022) - Devi, Ngasepam Monica; BaQais, Amal; Debnath, Anil Krishna; Alam, Mir Waqas; Singh, Naorem Khelchand
Abstract: This work reports the growth of an Ag@CeO2 nanorod (NR) composite array using the glancing angle deposition (GLAD) technique for UV photodetector application. It showed improvement in performance by decorating plasmonic nanoparticles (NPs) on the semiconductor surface. The interaction between the plasmonic NPs and the semiconductor under the influence of light manifested a localised surface plasmon resonance (LSPR) effect. This allowed for strong absorption, scattering and inducement of an intense electric field, which resulted in the enhancement of photocurrent and, consequently, the device performance. The use of the GLAD technique also allowed the growth of vertically oriented NR composite structures, which assisted in increased absorption. It was found that the fabricated structure exhibited an increase in the responsivity at 370 nm with a value of 18.74 AW -1 as compared to the previous work of only 4.51 AW -1 . A comparably high detectivity of 3.94 × 10 12 Jones and a low NEP value of 10.67 fW at −6 V were also exhibited by the device on account of low dark current and enhanced photocurrent. The maximum internal gain obtained for the device was 62.92. The presence of Ag NPs all around the semiconductor NR structure had led to a substantial increase in the photoresponse with a rise time and fall time of 65 ms and 58 ms respectively. These results are believed to offer new ways of harnessing light to boost the functioning of 1D nanostructure-based UV photodetectors.